Representing the exotic and the familiar : politics and perception in literature - Bharat, Meenakshi, 1959- (FILLM studies in languages and literatures ;, 2019)
"The multicultural world of today is often said to be marked by a certain kind of exoticization: a "fetishizing process", as Graham Huggan has called it, which separates a "first world" from a "third world", the Occident from the Orient. The essays collected here re-assess this tendency, not least by focusing on the kinds of intellectual tourism and dilettantism to which it has given rise. The wider context of these analyses is a postcolonial scenario where literatures and languages can move from the "exotic" to the comparatively "familiar" space of contemporary writings; where an exotic mythos can live on into the familiar present; and where certain perceptions and representations of peoples, of literatures, and of languages have turned exoticization and familiarization into global modes of mass-cultural consumption. Especially by exploring the liminalities between different cultures, this collection manages to trace both the history and the politics of exoticist representation and, in so doing, to make a significant critical intervention"--